アイスランド キョウヤク テン カンソク システム ノ シュウロク データ ヘンシュウ ショリ - 内田, 邦夫; ウチダ, クニオ; 利根川, 豊; トネガワ, ユタカ; 藤井, 良一; フジイ, リョウイチ; 佐藤, 夏雄; サトウ, ナツオ; Uchida, Kunio; Tonegawa, Yutaka; Fujii, Ryoichi; Sato, Natsuo (1988)
P(論文) 南極の昭和基地, みずほ基地, マラジョージナヤ基地の地磁気共役点であるアイスランドのHusafell, Isafjordur, Tjornesの3点において, 共役点観測が1983年8月(Husafell), 1984年9月(Isafjordur, Tjornes)より開始されている。観測項目中, 地磁気, ULF, VLF, CNA等の超高層モニタリングデータはアイスランド大学等の協力により通年観測が行われており, 収録データは1-2カ月ごとに計算機用磁気テープの形で国立極地研究所に郵送される。本データは利用者に供するために同研究所・情報処理センターの計算機システムで編集処理を行っているが, 編集処理は磁気テープが到着するごとに行う必要があり, その作業は定式化・簡略化されていることが重要である。このような目的に合った編集処理用プログラムを作成したので報告する。併せて編集データを利用する場合に必要な較正値等についても述べられる。 This paper reports the outline of the data acquisition system and the data compilatory program developed for geomagnetically conjugate observation of aurora and related phenomena being condcuted between three Antarctic stations and their geomagnetically conjugate stations in Iceland. The conjugate observation was initiated with Syowa (Antarctica)-Husafell (Iceland) pair in August 1983 and the observation was extended to other two pair stations of Mizuho (Antarctica)-Isafjordur (Iceland) and Molodezhnaya (Antarctica)-Tjornes (Iceland) in September 1984. The upper atmosphere physics data of the conjugate observation such as magnetic field, ULF, VLF and CNA have been continuously obtained in cooperation with Science Institute, University of Iceland. The recorded data are compiled using the computer system at the Information Processing Center, National Institute of Polar Research. The compilatory program has been developed in order to simplify the compilatory processes. A method of transformation from the digital data to physical units is also reported in this paper. departmental bulletin paper